Tracing shared genomic regions among local cattle breeds from Sardinia - Milia, Paola Erminia; Falchi, Laura; Cesarani, Alberto; Macciotta, Nicolo Pietro Paolo; Dimauro, Corrado (Frontiers in Animal Science, 2025)
Three local cattle breeds are farmed in the island of Sardinia (Italy): Sarda (SAR), Sardo-Bruna (SB), and Sardo-Modicana (SM). Historically, SAR was the Sardinian autochthonous breed, known for its resilience despite low productivity. To improve its performance, SAR cows were crossbred with Brown Swiss (BR) and Modicana (MOD) bulls, originating SB and SM. The aim of this research was to investigate how much SAR genomic background remains in SB and SM. A sample of 239 animals (64 SAR, 57 SM, 20 SB, 50 BR and 48 MOD) were genotyped using the 50K SNP Illumina BeadChip. Initially, univariate approaches were used to investigate the genomic relationship of SB and SM with SAR, MOD, and BR. Admixture analysis (K = 2) revealed a greater genetic similarity of SB with SAR than with BR, whereas SM showed a greater genetic proximity with MOD than with SAR. This was also reflected in the Weighted FST values: SAR and SB showed the lowest FST (0.015), confirming their closer relationship, whereas SB and BR showed the highest (0.058), consistent with their greater divergence. For SM, the FST with MOD (0.027) was lower than with SAR (0.030), supporting its closer affinity with MOD. SNP in ROH (SNPROH) analyses identified 21 genomic regions shared among Sardinian cattle breeds, where 3 genes (COMMD1, B3GNT2, and FAM161A) linked to environmental adaptation were found. Further analyses combining univariate and multivariate methods identified SNP with low discriminant power between SAR and the derived populations (SM and SB). Some of these regions overlapped with shared runs of homozygosity (ROHREP), and contained genes potentially associated with adaptation (CTNNA2, ITPR2, NTN1, and USP43). This study demonstrates that part of the SAR genome is still present in SB and SM, particularly in regions related to adaptive traits.